THE ROLE OF CUSTOMER EXPECTATIONS, PERCEIVED QUALITY, AND PERCEIVED VALUE IN DEVELOPING SATISFACTION AND CUSTOMER LOYALTY CASE STUDY: SHAMPO PRODUCTS - Sukma, Andhi; Roespinoedji, Roeshartono; Roespinoedji, Gusni (International Journal of Psychosocial Rehabilitation, 2020)
Business competition is increasingly fierce at this time, requires each company to develop appropriate strategies to maintain and strengthen its position to survive. Especially in the FMCG industry (Fast Moving Consumer Good) whose purchases are included in the repeat purchase category, where the level of consumer loyalty is low. Therefore, using the ACSI Model, research was conducted to prove the extent of the role of Customer Expectations (CE), Perceived Quality (PQ) and Perceived Value (PV) in building Customer Satisfaction (CS), and the extent of CS's role in building Customer Loyalty (CL) ) on shampoo products. This type of research is descriptive with descriptive survey research methods. Data obtained from the results of the distribution of questionnaires conducted on convenience sampling (the respondent is the person met). The results of data collection as a primary data source were obtained from a total sample of 125 respondents. While the method of analysis used is factor analysis and multiple regression analysis. The analysis shows that the role of CE in building CS is smaller than the role of PQ and PV, while the role of CS in building CL is quite large as well. Based on these results it can be concluded that consumer satisfaction also plays a role in building consumer loyalty in shampoo products. Where this means marketers need to also pay attention to the role of consumer satisfaction in building consumer loyalty as one of the strategies that can be used in the face of this very competitive competition.